Study The Anti-Asthmatic Activity of Guggulsterone In Ovalbumin-Induced Asthma In Rat - Ahmed, Zainab H.; H Zalzala, Munaf (Iraqi Journal of Pharmaceutical Sciences, 2021)
Asthma is a chronic in?ammatory respiratory disease associated with the changes of asthmatic airway structural that result from interact remodeling and in?ammatory processes lead to obstruction of airway. Guggulsterone (GS) is a bioactive compound and plant steroid present in guggul gum of Commiphora wightii, which has anti-inflammatory and antioxidant activities. This study designed to investigate of anti-inflammatory activity of gugglsterone in improvement of asthma. Forty eight healthy albino male rats divided to six groups, Group I: Control group (distal water), Group II: Positive control group (distal water) with sensitization, Group III: Guggulsterone (25 mg/kg/day) with sensitization, Group IV: Guggulsterone (50 mg/kg/day) with sensitization, Group V: Prednisolone (4.12 mg/kg/day) with sensitization, Group VI: Guggulsterone (50mg/kg/day) without sensitization. Rats were sacrificed and blood samples were collected to prepare of serum samples that used in ELISA kits for measuring of IL-4, IL-5, IL-33, TNF IgE. In addition, WBC counts in Bronchoalveolar lavage fluid. ALL parameters (IL-4, IL-5, IL-33, TNF, & IgE) levels for rats of treated groups with gugglsterone were significant (P<0.05) reduced in compared to sensitized group. Similarly, WBC count for rats treated groups with guggulsterone was significantly (P<0.05) fewer than sensitized group. In conclusion, our results provide a clue that guggulsterone has a potent anti-inflammatory activity that improved OVA-induced asthma and is useful for the preventive of allergic airway disease in rodents.